2003
DOI: 10.1002/jcp.10374
|View full text |Cite
|
Sign up to set email alerts
|

How to overcome (and exploit) tumor hypoxia for targeted gene therapy

Abstract: Tumor hypoxia has long been recognized as a critical issue in oncology. Resistance of hypoxic areas has been shown to affect treatment outcome after radiation, chemotherapy, and surgery in a number of tumor sites. Two main strategies to overcome tumor hypoxia are to increase the delivery of oxygen (or oxygen-mimetic drugs), or to exploit this unique environmental condition of solid tumors for targeted therapy. The first strategy includes hyperbaric oxygen breathing, the administration of carbogen and nicotinam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 152 publications
1
49
0
Order By: Relevance
“…Moreover, targeting gene expression to the hypoxic regions of solid tumors will allow the use of lower doses of the vector and decrease the risk of side effects. 26,27 In this respect, the successful performance of the E-M-H vector in LLC1 carcinoma cells should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targeting gene expression to the hypoxic regions of solid tumors will allow the use of lower doses of the vector and decrease the risk of side effects. 26,27 In this respect, the successful performance of the E-M-H vector in LLC1 carcinoma cells should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…The critical changes in the cellular microenvironment are due to an inadequate oxygen supply and the resultant hypoxia (2). The hypoxic tumor environment results in aggressive and metastatic cancer phenotypes that are associated with resistance to radiation therapy, chemotherapy, and a poor treatment outcome (3,4). Hypoxia detected in the central regions of solid tumors can be a leading cause of angiogenesis, a fundamental determinant of malignant tumor progression, by activating the expression of angiogenic factors (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…HSVtk/GCV and NTR/CB1954 have been widely used in a number of cytotoxic gene therapy studies, including therapies targeting hypoxia. [21][22][23][24] Only a few studies have compared both HSVtk and NTR systems in parallel, but none of these comparisons has been under hypoxic conditions with different transcriptional regulation. In one study, HSVtk/GCV showed the widest therapeutic index, whereas NTR/CB1954 demonstrated a stronger bystander effect in a retroviral vector.…”
Section: Discussionmentioning
confidence: 99%